The short-run effects of Knowledge intensive greenfield FDI on new domestic entry - Sara Amoroso; Bettina Müller (European Commission, Joint Research Centre (JRC), 2017)
Existing evidence on the impact of foreign direct investment on domestic economies remains ambiguous. Positive technology spillovers of foreign investment may be outweighed by negative crowding out effect due to increased competition. In this paper, we employ a unique country/sector-level data set to investigate the impact of what is considered the best type of foreign investment greenfield knowledge intensive FDI on domestic entry. Our results suggest that, in the short run, this type of FDI is positively related to the entry rate in the host country, if the domestic sector is either dynamic, or highly R&D intensive. These sectors may be respectively characterized by lower entry costs, which encourage a trial and error learning business approach, and by a higher level of absorptive capacity which increases the chance of technology transfer.
Keywords: L26; F21; O30; 330; foreign direct investments; knowlwdge spillovers; new firm entry